Ugotavljanje občutljivosti ultrazvočnega toplotnega merilnika s programskim paketom ANSYS - Boltežar, Marko (Strojniški vestnik, 2004)
In this paper an investigation of the sensitivity of an ultrasonic heat meter is presented. The goal of the investigation was to determine the shape of the flow measuring cell that gives the maximum sensitivity. The simulation involved the program package ANSYS, which is based on the finite-element method (FEM). The FEM results were experimentally verified. The simulations turned out to be very close to the actual flow conditions within the flow unitof the heat meter. The experimental results agree well with theory. The final result of the FEM analysis and the experimental measurements is a prototype of the measuring cell that ensures the required sensitivity of the heat meter.
Keywords: ANSYS; merilniki ultrazvočni; merilniki toplote; občutljivost; paketi programski; ultrazvočni merilniki; toplota; pretok; merjenje